Rib fracture management: A review of surgical stabilization, regional analgesia, and intercostal nerve cryoablation - Stephen Stopenski; Jana Binkley; Sebastian D. Schubl; Zachary M. Bauman (Surgery in Practice and Science, 2022)
Rib fractures still remain a common problem in blunt thoracic trauma, often resulting significant acute and/or chronic morbidity and mortality. The management of rib fractures has improved over the past two decades, resulting in overall improved patient outcomes. With advances in surgical stabilization of rib fractures (SSRF), improvements in regional analgesia, and the introduction of intercostal nerve cryoablation, patient outcomes from rib fractures have improved significantly over the past several years. This article explores the indications and technique for SSRF as well as discusses additional therapeutic modalities for rib fractures through regional anesthesia and intercostal nerve cryoablation.